Analysis of Income Tax Calculation at Rs Ummi Bengkulu City Based on Article 21 of Law Number 36 of 2008 concerning Income Taxes - Susena, Karona Cahya; Hidayah, Nenden Restu; Hendriansyah, Weko (Journal of Law, Social Science, and Management Review, 2025)
This research aims to analyze the calculation of Income Tax Article 21 in Law no. 36 of 2008 at Ummi Hospital, Bengkulu City. Using qualitative descriptive research methodology with the aim of providing the information needed to solve problems in the field in a specific, transparent and in-depth manner. Observation, interviews and documentation studies are the methods used to collect data. The research results show that the Ummi Hospital in Bengkulu City has complied well with Article 21 Income Tax obligations. Regarding the deposit and reporting of income tax Article 21, the Bengkulu City Ummi Hospital has fulfilled its responsibilities in a timely manner and in accordance with applicable law, where the Bengkulu City Ummi Hospital made the deposit and reporting of Article 21 Income Tax before the specified time limit. This is to avoid fines